Production of short-chain fructooligosaccharides (scFOS) using extracellular β-D-fructofuranosidase produced by Aspergillus thermomutatus - Tódero, Larissa Midiane [UNESP]; Rechia, Carem Gledes Vargas; Guimarães, Luis Henrique Souza (Hindawi, 2019)
Aspergillus thermomutatus produces an extracellular β-D-fructofuranosidase when cultured in Khanna medium with sucrose as additional carbon source at 30°C under agitation for 72 hr. Addition of glucose and fructose in the culture medium affected the production of the enzyme negatively. The optimum hydrolytic activity was achieved at 60°C and pH 5.0, with half-life (T50) of 30 hr at 50°C and 62% of its activity maintained at pH 5.0 for 48 hr. The extracellular extract containing β-D-fructofuranosidase was effective in producing fructooligosaccharides (FOS), mainly 1-kestose. The highest concentration of FOS was obtained at 30°C and 60°C, indicating the existence of at least two enzymes with transfructosylating activity. At 30°C, the maximal FOS concentration was obtained from 48 to 72 hr, while at 60°C, it was achieved only at 72 hr. The best production of FOS (86.7 g/L) was obtained using 500 g/L sucrose as substrate. Practical application: Fructooligosaccharides (FOS) are linear oligomers of fructose units with important applications in the food industry as sweetening agents and biopreservatives. Due to the presence of β-glycosidic bonds, they cannot be hydrolyzed by human enzymes, allowing the use of FOS-containing products by diabetics. FOS used in the preparation of dairy products imparts humectancy to soft baked products, lowers the freezing point of frozen desserts, provides crispness to low-fat cookies, and provides many other advantages. Diets containing FOS can reduce the levels of triglycerides and cholesterol and improve the absorption of ions, such as Ca2+ and Mg2+. FOS also exhibit bifidogenic effect on Bifidobacterium and Lactobacillus strains in the colon. Industrially, FOS is produced during the transfructosylation reaction of sucrose catalyzed by β-D-fructofuranosidase. Identifying new sources of β-D-fructofuranosidase is an important challenge to meet its industrial demand.
Keywords: Aspergillus; fructooligosaccharide; transfructosylating; β-D-fructofuranosidase